Self-incompatibility in Brassicaceae crops: lessons for interspecific incompatibility - Kitashiba, Hiroyasu (Japanese Society of Breeding, 2014)
Most wild plants and some crops of the Brassicaceae express self-incompatibility, which is a mechanism that allows stigmas to recognize and discriminate against “self” pollen, thus preventing self-fertilization and inbreeding. Self-incompatibility in this family is controlled by a single S locus containing two multiallelic genes that encode the stigma-expressed S-locus receptor kinase and its pollen coat-localized ligand, the S-locus cysteine-rich protein. Physical interaction between receptor and ligand encoded in the same S locus activates the receptor and triggers a signaling cascade that results in inhibition of “self” pollen. Sequence information for many S-locus haplotypes in Brassica species has spurred studies of dominance relationships between S haplotypes and of S-locus structure, as well as the development of methods for S genotyping. Furthermore, molecular genetic studies have begun to identify genes that encode putative components of the self-incompatibility signaling pathway. In parallel, standard genetic analysis and QTL analysis of the poorly understood interspecific incompatibility phenomenon have been initiated to identify genes responsible for the inhibition of pollen from other species by the stigma. Herewith, we review recent studies of self-incompatibility and interspecific incompatibility, and we propose a model in which a universal pollen-inhibition pathway is shared by these two incompatibility systems.